The Effect of a Vegetarian vs Conventional Hypocaloric Diabetic Diet on Thigh Adipose Tissue Distribution in Subjects with Type 2 Diabetes: A Randomized Study - Kahleova, Hana; Klementova, Marta; Herynek, Vit; Skoch, Antonin; Herynek, Stepan; Hill, Martin; Mari, Andrea; Pelikanova, Terezie (Journal of the American College of Nutrition, 2017)
OBJECTIVE: The aim of our study was to compare the effects of a vegetarian and a conventional diet on thigh adipose tissue distribution in subjects with type 2 diabetes (T2D). METHODS: Seventy-four subjects with T2D were randomly assigned to either follow a vegetarian diet (V, n = 37) or a control group who followed an isocaloric conventional anti-diabetic diet (C, n = 37). Both diets were calorie restricted (-500 kcal/day). To measure insulin sensitivity, the hyperinsulinemic (1 mU.kg-1.min-1) isoglycemic clamp was conducted. β-Cell function was assessed using a mathematical model after a test meal. Magnetic resonance imaging of the thigh was performed. All subjects were examined at 0, 3, and 6 months. Statistical analyses were performed using repeated measures analysis of variance and a multivariate regression model. RESULTS: Greater reduction was observed in total leg area in V (-13.6 cm2 [95% confidence interval [CI], -14.2 to -12.9] in V vs -9.9 cm2 [95% CI, -10.6 to -9.2] in C; Gxt p < 0.001). The reduction in subcutaneous fat was comparable in response to both diets (Gxt, p = 0.64). Subfascial fat was reduced only in response to a vegetarian diet (-0.82 [95% CI, -1.13 to -0.55] cm2 in V vs -0.44 [95% CI, -0.78 to +0.02] cm2 in C; Gxt, p = 0.04). The reduction in intramuscular fat tended to be greater in response to a vegetarian diet (-1.78 [95% CI, -2.26 to -1.27] cm2 in V vs -0.57 [95% CI, -1.06 to -0.09] cm2 in C; Gxt, p = 0.12). Changes in subcutaneous and subfascial fat correlated with changes in glycated hemoglobin (HbA1c), fasting plasma glucose, and β-cell insulin sensitivity. After adjustment for changes in body mass index (BMI), correlations remained significant for changes in fasting plasma glucose and β-cell insulin sensitivity and with changes in triglycerides. CONCLUSIONS: Our data indicate the importance of both subcutaneous and subfascial fat in relationship to glucose and lipid metabolism. ABBREVIATIONS: BMI , body mass index; C , control group; FPG , fasting plasma glucose; Gxt , interaction between group and time; HbA1c , glycated hemoglobin; MCR , metabolic clearance rate of glucose; OPLS , orthogonal projections to latent structure; T2D , type 2 diabetes; V , vegetarian group.
Keywords: Diet, Vegetarian; thigh adipose tissue; kalorická restrikce; Male; type 2 diabetes; intramuscular fat; tuková tkáň; Adult; Diabetes Mellitus, Type 2; dospělí; mužské pohlaví; diabetes mellitus 2. typu; Body Fat Distribution; Caloric Restriction; lidé; Adipose Tissue; ženské pohlaví; Humans; Energy Intake; dieta vegetariánská; vegetarian diet; Insulin sensitivity; energetický příjem; distribuce tělesného tuku; Female